2015
DOI: 10.1073/pnas.1502405112
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis DET1 degrades HFR1 but stabilizes PIF1 to precisely regulate seed germination

Abstract: Seed is an essential propagation organ and a critical strategy adopted by terrestrial flowering plants to colonize the land. The ability of seeds to accurately respond to light is vital for plant survival. However, the underlying mechanism is largely unknown. In this study, we reveal a circuit of triple feed-forward loops adopted by Arabidopsis seeds to exclusively repress germination in dark conditions and precisely initiate germination under diverse light conditions. We identify that de-etiolated 1 (DET1), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
65
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 37 publications
(69 reference statements)
2
65
0
Order By: Relevance
“…It is important to improve seed germination to maintain the sustainable development of agriculture (Bewley, 1997;FinchSavage and Leubner-Metzger, 2006;Holdsworth et al, 2008;Weitbrecht et al, 2011). Moreover, photomorphogenic regulators are involved in light-initiated seed germination in Arabidopsis (Shi et al, 2013(Shi et al, , 2015 and participate in phytohormone-controlled seedling growth Seo et al, 2009;Yu et al, 2013). In addition, increasing numbers of studies have revealed that ethylene suppresses SSG (Negm and Smith, 1978;Chang et al, 2010;Lin et al, 2012); however, it remains unclear whether the light signaling factor COP1 participates in SSG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to improve seed germination to maintain the sustainable development of agriculture (Bewley, 1997;FinchSavage and Leubner-Metzger, 2006;Holdsworth et al, 2008;Weitbrecht et al, 2011). Moreover, photomorphogenic regulators are involved in light-initiated seed germination in Arabidopsis (Shi et al, 2013(Shi et al, , 2015 and participate in phytohormone-controlled seedling growth Seo et al, 2009;Yu et al, 2013). In addition, increasing numbers of studies have revealed that ethylene suppresses SSG (Negm and Smith, 1978;Chang et al, 2010;Lin et al, 2012); however, it remains unclear whether the light signaling factor COP1 participates in SSG.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, light is a major environmental factor that affects seed germination (Borthwick et al, 1952;Seo et al, 2009). DE-ETIOLATED1 regulates the stabilization of LONG HYPOCOTYL IN FAR-RED1 (HFR1) and PHYTOCHROME INTERACTING FACTOR1 (PIF1), and the HFR1-PIF1 complex inversely modulates the entire genomic transcriptional network in phytochrome B-dependent seed germination (Shi et al, 2013(Shi et al, , 2015. CONSTITUTIVE PHOTOMOR-PHOGENESIS1 (COP1), a central repressor of light signaling, is a ring finger E3 ligase Torii et al, 1998;Jang et al, 2010;Osterlund et al, 2000;Yi and Deng, 2005), which itself is regulated by multiple factors (Zhong et al, 2009;Yu et al, 2013).…”
mentioning
confidence: 99%
“…Strikingly, PIF1 functions as a cofactor of the COP1 E3 Ubiquitin ligase and promotes substrate recruitment and auto-and transubiquitylation of HY5, thereby synergistically represses photomorphogenesis in the dark . In contrast, DET1 interacts with PIFs and stabilize them in the dark (Dong et al, 2014;Shi et al, 2015). Overall, PIFs interact with multiple unrelated proteins to modulate various signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…In Arabidopsis, of HFR1-PIF heterodimers that inhibit the promoter binding of the PIFs to their target genes (Hornitschek 427 et al, 2009;Lorrain et al, 2009;Shi et al, 2013;Shi et al, 2015). In addition, PIF4 and PIF5 directly 428 promote the expression of HFR1, thus forming a negative feedback loop ).…”
mentioning
confidence: 99%